Adenosine and its receptors in the heart: Regulation, retaliation and adaptation - Headrick, J.; Peart, J.; Reichelt, M.; Haseler, Luke (Elsevier, 2011)
The purine nucleoside adenosine is an important regulator within the cardiovascular system, and throughout the body. Released in response to perturbations in energy state, among other stimuli, local adenosine interacts with 4 adenosine receptor sub-types on constituent cardiac and vascular cells: A 1 , A 2A , A 2B , and A 3 ARs. These G-protein coupled receptors mediate varied responses, from modulation of coronary flow, heart rate and contraction, to cardioprotection, inflammatory regulation, and control of cell growth and tissue remodeling. Research also unveils an increasingly complex interplay between members of the adenosine receptor family, and with other receptor groups. Given generally favorable effects of adenosine receptor activity (e.g. improving the balance between myocardial energy utilization and supply, limiting injury and adverse remodeling, suppressing inflammation), the adenosine receptor system is an attractive target for therapeutic manipulation. Cardiovascular adenosine receptor-based therapies are already in place, and trials of new treatments underway. Although the complex interplay between adenosine receptors and other receptors, and their wide distribution and functions, pose challenges to implementation of site/target specific cardiovascular therapy, the potential of adenosinergic pharmacotherapy can be more fully realized with greater understanding of the roles of adenosine receptors under physiological and pathological conditions. This review addresses some of the major known and proposed actions of adenosine and adenosine receptors in the heart and vessels, focusing on the ability of the adenosine receptor system to regulate cell function, retaliate against injurious stressors, and mediate longer-term adaptive responses. Â© 2010 Elsevier B.V.